Vraževerje in čarovništvo v šentrupertskih povedkah - Smole, Vera (Traditiones (Ljubljana), 2017)
This paper is a discussion of the reflections of beliefs, superstitions, witchcraft and magic in folk tales gathered in the eastern Dolenjska municipality of Šentrupert. Until recently, at least some individuals there believed in witchcraft as something self-evident and malevolent as well as in the existence of persons who knew how to eliminate its negative consequences. This included tricking the highly personified "devil" (hudič), while protection against "(night)mare" (mora) has already disappeared from folk memory. The author also points out the similarities and differences to findings of broader research on village witchcraft in eastern Slovenia (Mencej 2006).
Keywords: čarovništvo; folk beliefs; ljudska verovanja; ljudske pripovedke; praznoverje; Slovenian folk literature; slovensko ljudsko slovstvo; superstition; Šentrupert; tales; witchcraft